PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (CSRD) TERHADAP RASIO PROFITABILITAS DAN EARNING RESPONSE COEFFICIENT (ERC) - Desra Tulhasanah; Nikmah Nikmah (Jurnal Akuntansi, 2017)
The focus of this study was to examine the effect of Corporate Social Responsibility Disclosure (CSRD) incompany’s annual report on Profitability Ratio and Earning Response Coefficient (ERC). The population of thisresearch is manufacturing firms listed in Indonesia Stock Exchange during 2013-2016. This is a quantitativeresearch which the data are analyzed by using multiple linier regression method. Profitability ratio, which in thiscase assessed by proxy Return On Asset, Return On Equity and Net Profit Margin. The result of this research provethat CSRD has significant positive effect on ROA and ROE. Beside, CSRD doesn’t influence NPM and ERC.Therefore, this research was examine the effect of CSRD on profitability ratio and ERC with size and leverage ascontrol variable.Keywords: Corporate Social Responsibility Disclosure (CSRD), Return On Asset, Return On Equity, Net ProfitMargin, Earning Response Coefficient, Size, Leverage.